2018
DOI: 10.1016/j.phrs.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome in chronic kidney disease patients undergoing hemodialysis and peritoneal dialysis

Abstract: Chronic kidney disease (CKD) is associated with an imbalanced human microbiome due not only to CKD-associated factors such as uremia, increased inflammation and immunosuppression, but also to pharmacological therapies and dietary restrictions. End-stage renal disease patients require renal replacement therapies commonly in the form of hemodialysis (HD) or peritoneal dialysis (PD). HD implies the existence of a vascular access, such as an arteriovenous fistula/graft or a venous catheter, whereas PD implies a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 127 publications
2
47
0
Order By: Relevance
“…The gut microbiome patterns in patients with dialysis‐dependent end‐stage kidney disease have been well documented in the literature. Compared with healthy individuals, haemodialysis patients exhibited a higher proportion of Proteobacteria, Actinobacteria and Firmicutes . Additionally, faecal analysis demonstrated reduced proportions of bacteria that were able to produce short chain fatty acid butyrate, which is known to be associated with immune regulation, iron absorption, inflammatory and oxidative stress and cell growth and differentiation .…”
Section: Gastrointestinal Microbiotamentioning
confidence: 99%
See 2 more Smart Citations
“…The gut microbiome patterns in patients with dialysis‐dependent end‐stage kidney disease have been well documented in the literature. Compared with healthy individuals, haemodialysis patients exhibited a higher proportion of Proteobacteria, Actinobacteria and Firmicutes . Additionally, faecal analysis demonstrated reduced proportions of bacteria that were able to produce short chain fatty acid butyrate, which is known to be associated with immune regulation, iron absorption, inflammatory and oxidative stress and cell growth and differentiation .…”
Section: Gastrointestinal Microbiotamentioning
confidence: 99%
“…Compared with healthy individuals, haemodialysis patients exhibited a higher proportion of Proteobacteria, Actinobacteria and Firmicutes. [31][32][33][34] Additionally, faecal analysis demonstrated reduced proportions of bacteria that were able to produce short chain fatty acid butyrate, which is known to be associated with immune regulation, iron absorption, inflammatory and oxidative stress and cell growth and differentiation. 35 In contrast, compared with individuals without end-stage kidney disease, peritoneal dialysis (PD) patients displayed a reduced abundance of Firmicutes and Actinobacteria, and an increased abundance of Proteobacteria.…”
Section: Gastrointestinal Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that patients with ESRD have expansion of Firmicutes, Actinobacteria and Proteobacteria phyla and reduction of Bifidobacteria and Lactobacilli populations in their colons [9]. Several studies have also uncovered marked alteration of the microbiota composition in hemodialysis patients [10]. Alterations in microbiome composition results in increased generation of lipopolysaccharide, IS, p-CS, amines and ammonia that lead to the activation of proinflammatory cytokine/chemokine cascades in CKD and ESRD [11].…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in the normal gut microbiome are currently associated with the pathogenesis of several chronic diseases, including chronic kidney disease (CKD) [4][5][6][7][8][9][10][11][12]. Gut dysbiosis is well-described in CKD, characterized by lower levels of Bifidobacteriaceae and Lactobacillaceae and higher levels of Enterobacteriaceae [13,14]. The composition of this microbiome is also affected by renal replacement therapy (RRT) used by patients with end-stage kidney disease (ESKD).…”
Section: Introductionmentioning
confidence: 99%